Brefeldin A exerts differential effects on anaplastic lymphoma kinase positive anaplastic large cell lymphoma and classical Hodgkin lymphoma cell lines. (24th June 2015) - Toda, Takashi; Watanabe, Mariko; Kawato, Junji; Kadin, Marshall E.; Higashihara, Masaaki; Kunisada, Takao; Umezawa, Kazuo; Horie, Ryouichi
Summary To obtain further insights into the biological differences of anaplastic lymphoma kinase positive anaplastic large cell lymphoma (ALK+ ALCL) and classical Hodgkin lymphoma (HL), we screened microbial culture filtrates to search for compounds that would exert a significantly greater effect on the viability of ALK+ ALCL cell lines compared to HL cell lines and identified Brefeldin A (BFA) as a suitable candidate. BFA inhibited phosphorylation of ALK and its downstream molecule, signal transducer and activator of transcription 3 (STAT3), one of the central pathways for the survival of ALK+ ALCL cells. In HL cell lines BFA did not affect CD30 expression or constitutive nuclear factor (NF)‐κB activity, both of which are critical for HL cell survival. BFA induced disruption of the Golgi apparatus in ALK+ ALCL cell lines, which was accompanied by a decrease in active ADP‐ribosylation factor 1 (ARF1), whereas BFA had no significant effect on these parameters in HL cell lines. These results add extra insights into the biological distinction between ALK+ ALCL and HL cells and highlight the Golgi apparatus as a target for the treatment of ALK+ ALCL.